Wisdom of the Gods for you and me : My Gita and my Hanuman Chalisa - Devdutt Pattanaik (Rupa, 2019)
Devdutt Pattanaik is an exponent of myths, using them [to] deepen storytelling, and obtain a sense of life and living’ —Scroll.in Hindu mythology is vast and voluminous. There is so much we don’t know or that has not been presented in a simplified way, making sense to contemporary times. This special omnibus edition brings together two bestselling books by Devdutt Pattanaik, India’s most famous and renowned mythologist. My Gita and My Hanuman Chalisa are part of a series where Devdutt does ‘darshan’ of the scriptures, not just gods, and helps readers navigate through scriptures that seem forbidding (Bhagavad Gita) and simple ones whose sophistication is often overlooked (Hanuman Chalisa).